Design a novel g-C3N4 based Ce2O3/CuO ternary photocatalysts for superior photo-degradation performance of organic mixed pollutants: Insights of Z-scheme charge transfer mechanism. (March 2022) - Vignesh, Shanmugam; Suganthi, Sanjeevamuthu; Palanivel, Baskaran; Ali, Atif Mossad; Shkir, Mohd; Algarni, H.; Sreedevi, Gedi
Abstract: In this work, a novel ternary g-C3 N4 /Ce2 O3 /CuO (GCC) composite photocatalyst was effectively synthesized by facile calcination and dynamic hydrothermal technique. The as-obtained photocatalysts (PCs) samples were characterized using several techniques such as XRD, FT-IR, FESEM-EDAX with mapping, HR-TEM, high-resolution XPS, UV-DRS absorption and PL spectra respectively. The photo-degradation outcomes specified that the ternary GCC composite PCs possessed the better photocatalytic efficiency by degrading for the aqueous MY (94.5%) and MB (90.3%) mixed dye compared to other as-obtained PCs samples within 150 min under visible-light exposure. Moreover, after the fifth recycles of the superior GCC composite PCs, the photo-degradation rate of MB and MY mixed dyes still could be reached to 81% and 86.5%, respectively, which revealed the excellent reusability and photostability after the five successive recycles. Hence, the improved photo-degradation activity could be ascribed to a lower bandgap, superior visible-light absorption capacity and reduced the recombination rate of photo-excited electron-hole (e − /h + ) pairs among the synergistic effects of unique g-C3 N4, Ce2 O3 and CuO heterointerface in the efficient three-level e − /h + transfer. Based on the various scavenger's tests, a probable charge transfer pathway with the strong reduction ability process was also proposed. The superior photo-degradation efficiency and their probability, which make reusable PCs and a potential aspirant for environmental wastewater purification and energy conversion. Highlights: A novel g-C3 N4 /Ce2 O3 –CuO composite was successfully prepared by a facile method. The degradation rate of MY and MB mixed dyes reached 94.5% and 90.3% in 150 min. The rate constant of ternary PCs reached about 4.7 and 4.58 folds superior to GCN. Optimum CuO NPs was effectively incorporated on the g-C3 N4 /Ce2 O3 composite surface. The probable Z-scheme heterojunction charge transfer pathway was also proposed.